Workshop on Producing and Marketing Dishwashing Liquid - Nia Anggraini; Muhammad Adrian; R. Rudi Alhempi; Lussianda, Erfa Okta; Liga Febrina; Fahrozi, Muhammad (Indonesian Journal of Society Development, 2024)
This community service aimed to empower housewives in Lembah Sari Rumbai Timur, Pekanbaru, by providing training on liquid dish soap production and marketing strategies. The program included counseling, hands-on training, discussions, and marketing guidance. A total of 35 participants attended the training on November 24, 2022, at the Al-Mukarramah Multi-purpose Hall. The methods employed helped participants gain practical skills in soap-making and marketing. The program successfully enhanced participants' economic potential, contributing to family welfare and providing a replicable model for other regions. The findings suggest that skill-based empowerment can improve economic conditions and create entrepreneurial opportunities for housewives